2019
DOI: 10.1103/physrevlett.123.038004
|View full text |Cite
|
Sign up to set email alerts
|

Competing Timescales Lead to Oscillations in Shear-Thickening Suspensions

Abstract: Competing time scales generate novelty. Here, we show that a coupling between the time scales imposed by instrument inertia and the formation of inter-particle frictional contacts in shear-thickening suspensions leads to highly asymmetric shear-rate oscillations. Experiments tuning the presence of oscillations by varying the two time-scales support our model. The observed oscillations give access to a shear-jamming portion of the flow curve that is forbidden in conventional rheometry. Moreover, the oscillation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 42 publications
10
56
0
Order By: Relevance
“…S-shaped flow curves, and more generally rheograms with a negatively sloped region, are known to produce unstable flow conditions 35,36 . Previous studies on shear-thickening suspensions have based their analysis on this feature to explain for instance the emergence of random fluctuations 37 reported initially by Boersma et al 38 , and the oscillations observed when an object moves in a shearthickening fluid 39,40 or in rheometric configurations 15,41 . However, all these models require inertia to predict an instability.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…S-shaped flow curves, and more generally rheograms with a negatively sloped region, are known to produce unstable flow conditions 35,36 . Previous studies on shear-thickening suspensions have based their analysis on this feature to explain for instance the emergence of random fluctuations 37 reported initially by Boersma et al 38 , and the oscillations observed when an object moves in a shearthickening fluid 39,40 or in rheometric configurations 15,41 . However, all these models require inertia to predict an instability.…”
Section: Resultsmentioning
confidence: 98%
“…As a result, highly concentrated shear-thickening suspensions have peculiar S-shape rheological laws 9,10 , which have been rationalized by a frictional transition model 3,11,12 . So far, the consequences of the frictional transition and its associated S-shape rheology have been essentially investigated in rheometers, where instabilities, shear bands and spatiotemporal patterns have been documented 11,[13][14][15] . By contrast, very little is known about the behavior of shearthickening suspensions in real hydrodynamic flow configurations beyond rheometry, in spite of the numerous applications [16][17][18] .…”
mentioning
confidence: 99%
“…Cornstarch in aqueous media is a model for the rheology of purely repulsive nB suspensions, showing characteristic friction-driven shear thickening at a fixed onset stress 9,25 . When cornstarch is dispersed in non-aqueous solvents, shear thickening is no longer observed and a finite yield stress arises 26,27 .…”
Section: Experimental System and Methodsmentioning
confidence: 99%
“…The frictionless and frictional jamming points of cornstarch in aqueous solvents are φ rcp ≈ 0.60 29 and φ rlp ≈ 0.50 respectively. The latter is estimated from multiplying φ rlp ≈ 0.6 for non-aqueous cornstarch by the measured weight-fraction ratio of 0.84 for random loose to random close packing for aqueous cornstarch 9 . We therefore take the φ ≈ 0.54 at which σ (ss) y (φ) → ∞ to be the frictional jamming point, φ rlp , of cornstarch in oil.…”
Section: The Steady-state Yield Stressmentioning
confidence: 99%
“…This highlights the fact that σ, calculated from the torque applied to the tool, is not the average stress at the boundary of the suspension when the rotation rate varies, because of the inertia of the tool. Thus the dramatic stress fluc- tuations revealed by BSM are missed in standard bulk rheology, although they can be inferred from the changes in shear rate with quantitative modeling that incorporates the inertia of the rheometer tool [30][31][32]. Figure 7A shows σ BSM (black circles) for single event, along withγ (red triangles) and the normal force (F N , blue squares), at an applied stress of σ = 180 Pa.…”
Section: Constant Stress Measurementsmentioning
confidence: 99%